Fluctuation in body composition and urine specific gravity of Turkish wrestlers in a top-level official wrestling competition - Donmez, Ersel; Isik, Ozkan; Baic, Mario (Frontiers in Physiology, 2025)
PurposeThis research aimed to examine the fluctuations in body composition and Urine-Specific Gravity (USG) of elite wrestlers in a high-level official wrestling competition.MethodThirty-one wrestlers in the Türkiye Senior Greco-Romen Wrestling national team participated in this research. Wrestlers were divided into weight loss and non-weight loss groups, and changes in their body composition and USG were measured at three different times (beginning of the camp, weigh-in, and before the competition). The duration between the beginning of the camp and the competition weigh-in time was considered as a dehydration process and the duration between the competition weigh-in time and before the competition was regarded as a rehydration process. In the data analysis, 3 × 2 repeated measures ANOVA was used.ResultsIt was determined that during the dehydration process of wrestlers who lost weight, there was a decrease of 4.02%, 2.50%, 14.62%, and 2.66% in body weight, FFM, FM, and TBW, whereas, during the rehydration process, there was a gain of 1.85%, 1.77%, 2.63%, and 1.87%, respectively. In addition, it was determined that wrestlers who lost weight had a 0.87% increase in USG during the dehydration process and a 0.41% decrease in the rehydration process. The results show that wrestlers cannot regain body weight and FM lost in the hydration fluctuation during a competition, but they can regain FFM, TBW, and USG. However, although it was determined that the wrestlers were statistically able to regain FFM, TBW, and USG, they could not return to the levels at the beginning of the camp.ConclusionIt was determined that before a high-level official wrestling competition, wrestlers still preferred weight loss practices and it was determined that they were exposed to fluctuations in their body composition and USG. It is thought that this result may negatively affect the wrestlers’ health and competition performance during a high-level competition.